Artikel PENCIPTAAN KARYA SENI TEATER PAKELIRAN “JARATKARU”: PENCIPTAAN KARYA SENI TEATER PAKELIRAN “JARATKARU” - Suryanata I Putu Gede suryanata; Ni Komang Sekar Marhaeni; I Gusti Ngurah Gumana Putra; Ni Luh Ayu Cempaka Dewi (JURNAL DAMAR PEDALANGAN, 2026)
This article discusses the creation of the Teater Pakeliran Jaratkaru as an artistic output within the ISI Bali Berdampak Independent Project program. The work integrates theatrical performance and Balinese wayang tradition by using a warung (penggak) as a narrative frame to reflect contemporary Balinese social dynamics. The purpose of this creation is to reinterpret a classical story from Adi Parwa in order to address current issues related to patriarchy, lineage, and lifelong education. The creative process employed the Panca Stiti Ngawi Sani method, consisting of ngawirasa, ngewacak, ngarencana, ngawangun, and ngebah. The results show that the integration of theatre and pakeliran effectively contextualizes classical narratives, making them more communicative and relevant to modern audiences while preserving traditional aesthetic values. This work also embodies Balinese cultural concepts, including patriarchal inheritance systems and the Hindu philosophy of Catur Asrama as lifelong education. Furthermore, the creation of Jaratkaru is projected to generate social, environmental, and economic impacts, such as fostering intergenerational dialogue, strengthening ecological awareness based on Tri Hita Karana, and contributing to the sustainability of the performing arts ecosystem. This study implies that practice-based artistic research can serve as an effective medium for cultural reflection and community engagement in future artistic productions.